Abdominal T2‐Weighted Imaging and T2 Mapping Using a Variable Flip Angle Radial Turbo Spin‐Echo Technique. Issue 1 (13th July 2021) - Keerthivasan, Mahesh B.; Galons, Jean‐Philippe; Johnson, Kevin; Umapathy, Lavanya; Martin, Diego R.; Bilgin, Ali; Altbach, Maria I.
Abstract : Background: T2 mapping is of great interest in abdominal imaging but current methods are limited by low resolution, slice coverage, motion sensitivity, or lengthy acquisitions. Purpose: Develop a radial turbo spin‐echo technique with refocusing variable flip angles (RADTSE‐VFA) for high spatiotemporal T2 mapping and efficient slice coverage within a breath‐hold and compare to the constant flip angle counterpart (RADTSE‐CFA). Study Type: Prospective technical efficacy. Subjects: Testing performed on agarose phantoms and 12 patients. Focal liver lesion classification tested on malignant ( N = 24) and benign ( N = 11) lesions. Field Strength/Sequence: 1.5 T/RADTSE‐VFA, RADTSE‐CFA. Assessment: A constrained objective function was used to optimize the refocusing flip angles. Phantom and/or in vivo data were used to assess relative contrast, T2 estimation, specific absorption rate (SAR), and focal liver lesion classification. Statistical Tests: t ‐Tests or Mann–Whitney Rank Sum tests were used. Results: Phantom data did not show significant differences in mean relative contrast ( P = 0.10) and T2 accuracy ( P = 0.99) between RADTSE‐VFA and RADTSE‐CFA. Adding noise caused T2 overestimation predominantly for RADTSE‐CFA and low T2 values. In vivo results did not show significant differences in mean spleen‐to‐liver ( P = 0.62) and kidney‐to‐liver ( P = 0.49) relative contrast between RADTSE‐VFA and RADTSE‐CFA. Mean T2 values were not significantly different between the two techniques for spleen (T2VFA = 109.2 ± 12.3 msec; T2CFA = 110.7 ± 11.1 msec; P = 0.78) and kidney‐medulla (T2VFA = 113.0 ± 8.7 msec; T2CFA = 114.0 ± 8.6 msec; P = 0.79). Liver T2 was significantly higher for RADTSE‐CFA (T2VFA = 52.6 ± 6.6 msec; T2CFA = 60.4 ± 8.0 msec) consistent with T2 overestimation in the phantom study. Focal liver lesion classification had comparable T2 distributions for RADTSE‐VFA and RADTSE‐CFA for malignancies ( P = 1.0) and benign lesions ( P = 0.39). RADTSE‐VFA had significantly lower SAR than RADTSE‐CFA increasing slice coverage by 1.5. Data Conclusion: RADTSE‐VFA provided noise‐robust T2 estimation compared to the constant flip angle counterpart while generating T2‐weighted images with comparable contrast. The VFA scheme minimized SAR improving slice efficiency for breath‐hold imaging. Level of Evidence: 2 Technical Efficacy Stage: 1